Morphology of time data management – systematic design of time data management processes as fundamental challenge in industrial engineering. (1st January 2014) - Kuhlang, Peter; Erohin, Olga; Krebs, Matthias; Deuse, Jochen; Sihn, Wilfried
During the last 10 to 15 years, a renaissance of industrial engineering can be observed in manufacturing industry, as well as in scientific research. As a consequence, time and motion studies (TMS) become more important again. During the downturn of methodical approaches in industrial engineering in the 1980s, TMS-related competencies were lost in industry. Many companies are still missing the know-how for establishing a proper time data management (TDM). This paper presents a morphology of time data management (MoTDM), which was developed in order to create a comprehensive view on the processes of TDM as well as to detect relevant areas of improvement. The MoTDM can be used to optimise TDM processes within a company and also acts as scientific fundament for research in the field of industrial engineering.